Mind-Body Problem: Investigating the Gap Between Physiological and Perceived Stress Using Smartwatch Data - Salo, Petri (2024)
The popularity of physiological sensors is rising, with more people using smartwatches to monitor stress and optimize performance based on physiological data. However, recent studies show that physiological stress often differs from perceived stress, which can lead users to misinterpret these signals and make detrimental health decisions. This study investigated factors contributing to this discrepancy and the mechanisms underlying perceived stress. A multilevel linear mixed-effects model was applied to examine the relationship between perceived and physiological stress and to evaluate the moderating effects of attentional styles, the Big Five personality traits, and metacognitive beliefs on this relationship. Self-report questionnaires were used to assess these psychological factors and perceived stress. Physiological stress was measured daily for one month using Garmin smartwatches in a sample (N = 5) of highly educated adults aged 28–45. Results indicated no association between physiological and perceived stress nor moderation by attentional styles, personality traits, or metacognitive beliefs. Exploratory findings suggested that conscientiousness, extraversion, and metacognitive beliefs predicted perceived stress. Understanding how users interpret and trust physiological stress measurements is vital for developing user-friendly technologies that support informed decision-making and promote well-being. Despite its limitations, this study proposes a methodology for identifying factors influencing the relationship between physiological and perceived stress.